Responses of Gulf States to the Palestine-Israel conflict in post 7th October 2023 - Nasruddin Khalid,; Bakri Mat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The events of 7th October 2023 marked a turning point in Middle Eastern geopolitics, prompting Gulf Cooperation Council (GCC) states to reassess their foreign policy approaches to the escalating Israel-Palestine conflict. This study explores shifts in GCC foreign policies post-escalation through the lens of Realist theory, focusing on national interests, security concerns, and state survival amid regional instability. Employing qualitative methods, including historical analysis and data triangulation, the research analyses policy statements, reports, and scholarly sources to uncover the motivations behind individual state actions. The findings reveal significant disparities in GCC responses. Saudi Arabia suspended normalisation talks with Israel to align with pro Palestinian sentiment, while Qatar intensified mediation efforts and expanded humanitarian support. The UAE and Bahrain, balancing diplomatic ties with Israel and public concerns, adopted more cautious stances. Oman maintained neutrality, while Kuwait upheld a strongly pro-Palestinian position. The lack of unified GCC action highlights the bloc's fragmented nature, driven by diverging national priorities and geopolitical alliances. This study sheds light on the complexities of GCC diplomacy and its limitations in formulating a cohesive response to the conflict. By examining these dynamics, the research provides insights into regional geopolitics and proposes strategies to foster unity within the GCC, enhancing its role in addressing the Palestine-Israel conflict and broader regional challenges.